2023
DOI: 10.3389/fpsyg.2023.1016125
|View full text |Cite
|
Sign up to set email alerts
|

The chameleon effect in customer relationship management: Experiments on the spillover effects of mimicry in natural settings of a chain hotel and a chain grocery shop

Abstract: Numerous experiments have proven that mimicry is highly beneficial (mainly to the mimicker but also to the mimickee). Some studies have shown initial data suggesting the potential of applying this knowledge to business settings. In the present paper we unpack this issue in two ways. First, by presenting potential benefits stemming from mimicry for the mimicking dyad, and second for the business environment represented by the mimicker. Two consecutive studies: a Pretest and a Main Experiment run in natural sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Furthermore, research has shown that the effects of mimicry are even more far-reaching. A salesperson or receptionist who mimics another person is not only viewed more positively by the person being mimicked, but also positively influences the perception of the entire organization they represent [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research has shown that the effects of mimicry are even more far-reaching. A salesperson or receptionist who mimics another person is not only viewed more positively by the person being mimicked, but also positively influences the perception of the entire organization they represent [ 74 ].…”
Section: Discussionmentioning
confidence: 99%